A = 100 – l 6 – 2x l B = -6 – l x – 1 l – 2l y +9 l

A = 100 – l 6 – 2x l
B = -6 – l x – 1 l – 2l y +9 l

0 bình luận về “A = 100 – l 6 – 2x l B = -6 – l x – 1 l – 2l y +9 l”

  1. A = 100 – l 6 – 2x l

      TH1:l 6 – 2x l =6-2x

      ⇒A = 100 –  6 + 2x 

            =2x+94

      TH2: l 6 – 2x l =2x-6

       ⇒A = 100 – ( 2x -6)

             = 100-2x+6

             = 106-2x

    Bình luận
  2. Đáp án:

     

    Giải thích các bước giải:

     A=100 -|6-2x|

    TH1:

    A=100-6+2x

    =94 +2x

    TH2:A =100 +6 -2x

    =106 -2x

    B=-6 -|x-1| -2|y+9|

    TH1: B= -6 -x+1 -2y-18

    =-x -2y -23

    TH2: B=-6 +x-1+2y +18

    =x +2y +11

    Bình luận

Viết một bình luận